Kampus Mengajar: Upaya Pendampingan Pendidikan Era Pandemi Covid-19 di Desa Kalampadu Ogan Ilir - Yulasteriyani Yulasteriyani; Gita Isyanawulan; Isma Nurillah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
This service is motivated by the socio-cultural phenomenon of education in Kalampadu Village since the distance school system has created new social problems. The quality of school resources, parental resources, online media, and internet access does not support the learning process, causing children to find it challenging to understand school subject matter. This socio-cultural-educational problem should not be left without efforts to solve the problem because the nation's children are the hope and successor in a prosperous future of Indonesia. The Unsri community service team helped solve this educational problem by conducting socialization and internalization of socio-cultural-educational. This community service activity was carried out at the Village Hall, Kalampadu Village, involving 32 participants consisting of parents, teachers, students, community leaders, and the village government. This method is carried out by delivering material and direct practice to the participants of service activities. The results of these activities are full of practice from Parsons' structural, functional theory. Every series of events from beginning to end fits perfectly with the AGIL scheme in socializing and internalizing educational norms. Welcoming remarks as a process of re-adaptation, delivery of material according to the re-integration scheme, and a question-and-answer and interactive process is applying all elements of adaptation-achievement of goals-integration-maintenance of patterns. This service activity integrates the socio-cultural system of education towards an ideal and prosperous educational, social system.